Role Stress Auditor in Performance by Integrating The Concept of Whistleblowing Intention - Ni Putu Riski MARTINI; Gde Deny LARASDIPUTRA (International Journal of Environmental, Sustainability, and Social Science, 2020)
The importance of the whistleblowing concept to provide complaints related to fraud in the company. The study was conducted to determine the effect of role stress on auditors' performance with whistleblowing intention as a moderating variable. Quantitative research approach. The sampling technique was purposive sampling technique so that the research sample was 71 public accounting firms in Bali. The data analysis technique used multiple linear regression with moderated regression analysis (MRA) techniques. Determination of the sample using a purposive sampling technique. This study uses a questionnaire in data collection. The data analysis technique in this study is Multiple Linear Regression using the SPSS (Statistical Package for Social Science) application. The result of the research states that the relationship between the role of auditors' work stress can affect the performance of auditors and the relationship between whistleblowing intention, role stress affects the performance of auditors, so that it can avoid conflicts with auditors.